PROCESSING TEMPERATURE AND NUTRITIONAL QUALITY OF Moringa oleifera LEAVES: A COMPARATIVE ANALYSIS OF 30°C VERSUS 50°C - Aris Fitriyani; Maisje Marlyn Kuhu; Widjijati Widjijati (Universitas Negeri Gorontalo, 2026)
Moringa oleifera leaves are widely recognized as a rich source of protein, vitamins, minerals, and bioactive compounds with potential health benefits. However, drying temperature may influence their nutritional composition and bioactive properties, making the selection of an appropriate processing condition essential. Although previous studies have investigated the effects of drying on moringa leaves, limited information is available regarding the simultaneous evaluation of total tannin and essential minerals under low-temperature (30°C) and moderate-temperature (50°C) drying conditions. Therefore, this study contributes to existing knowledge by providing an integrated comparison of these quality parameters. This study aimed to compare the effects of processing temperatures of 30°C and 50°C on the nutritional content of moringa leaves. A laboratory experimental design was applied, with moringa leaves processed at the two drying temperatures. The measured parameters included total tannin and the mineral contents of magnesium (Mg), sodium (Na), calcium (Ca), potassium (K), and iron (Fe). Data were analyzed quantitatively to compare nutrient composition between treatments. The results showed that Moringa oleifera leaf powder dried at 50°C had higher measured concentrations of total tannin, Mg, Na, Ca, K, and Fe than that dried at 30°C. These findings indicate that moderate-temperature drying can enhance the measured retention of both bioactive compounds and minerals. Overall, drying at 50°C can be considered a practical processing condition for producing moringa leaf powder with higher measured tannin and mineral contents while maintaining processing efficiency for food and dietary supplement applications.